More affiliate information to schedule an area evacuation, area evacuation And keep it in French, and its effectiveness (Journal of the College of Basic Education, 2022)
Examinations have become a regulating force that directs the work of both the teacher and the student. So I gainedExaminations and evaluation methods are of great importance in the educational field. If the exams get worse, then the education gets worse.If reformed, this would be a means to reform its curriculum, just as the methods of examinations and evaluation have made great progress.at the present time. Evaluation became inseparable from the educational process, and it has a diagnostic and therapeutic function that helpsto correct its course. At the present time, the calendar is characterized by comprehensiveness, objectivity, and diversity.